A correlation study of the HSGA, NCEE scores and the CGPA of selected college freshmen of Divine Word University 1975-1976 and its implications to the school's career guidance program - Guzman, Orlando G. (Animo Repository, 1977)
This study attempts to determine the relationship of the HSGA and NCEE scores with academic performance as revealed by the grade point averages of 203 enrolled freshmen students of the colleges of commerce, engineering, liberal arts, nursing and the sciences enrolled at Divine Word University of Tacloban for the school year 1975-1976. It also aimed : 1. to find out how useful the HSGA and NCEE results are for the prediction of college freshmen success and 2. to produce an expectancy table which could be used in the schools guidance program. From the data gathered from the Registrars Office, the correlation aspect between the NCEE standard scores, high school general average (HSGA) and the college grade point average (CGPA) were then describe and analyze, using the Pearson's product-moment method and the partial and multiple correlation. Two specific areas were also studied, namely: English and mathematics.